Inclusion - leave no one behind: Pastoralism, pathways to prosperity - Jameel Observatory for Food Security Early Action (International Livestock Research Institute, 2024)
This poster uses photos taken by Nick Danziger for the Jameel Observatory. It is co-produced with Community Jameel